Development and initial validation of a measure of metacognitive beliefs in health anxiety: The MCQ-HA. Issue 3 (30th December 2015) - Bailey, Robin; Wells, Adrian
Abstract: Metacognitive beliefs have been shown to correlate with emotional disorders and more recently have been implicated in health anxiety. Research exploring these beliefs have tended to use the Metacognition Questionnaire (MCQ), which is a general measure. To facilitate research on the metacognitive model applied to health anxiety the present study reports on the development and initial evaluation of a new specific metacognitive measure of health anxiety, the Metacognitions Questionnaire-Health Anxiety (MCQ-HA). Principal components analysis identified 14 suitable items to be explored. Subsequent exploratory factor analysis of the MCQ-HA identified three factors: "Beliefs that Thoughts can cause Illness", "Beliefs about Biased thinking", and "Beliefs that Thoughts are Uncontrollable". Confirmatory factor analysis supported the three factor model with all selected goodness-of-fit statistics equivalent to or better than recommended values. Preliminary evidence suggests good internal-consistency, incremental, convergent and discriminant validity in relation to associated measures. The MCQ-HA appears to be a potentially useful predictor of health anxiety. Highlights: We developed a measure to assess metacognitive beliefs in health anxiety (MCQ-HA). Items were screened using principal components analysis. Exploratory factor analysis revealed a three factor solution. Confirmatory factor analysis supported the structure of the measure. The measure demonstrated reliability and validity.